Frequency of Epstein-Barr virus DNA sequences in human gliomas - Fonseca, Renata Fragelli; Rosas, Siane Lopes Bittencourt; Oliveira, José Antônio; Teixeira, Anselmo; Alves, Gilda; Carvalho, Maria da Glória Costa (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: The Epstein-Barr virus (EBV) is the most common cause of infectious mononucleosis and is also associated with several human tumors, including Burkitt’s lymphoma, Hodgkin’s lymphoma, some cases of gastric carcinoma and nasopharyngeal carcinoma, among other neoplasms. The aim of this study was to screen 75 primary gliomas for the presence of specific EBV DNA sequences by means of the polymerase chain reaction (PCR), with confirmation by direct sequencing. DESIGN AND SETTING: Prevalence study on EBV molecular genetics at a molecular pathology laboratory in a university hospital and at an applied genetics laboratory in a national institution. METHODS: A total of 75 primary glioma biopsies and 6 others from other tumors from the central nervous system were obtained. The tissues were immediately frozen for subsequent DNA extraction by means of traditional methods using proteinase K digestion and extraction with a phenol-chloroform-isoamyl alcohol mixture. DNA was precipitated with ethanol, resuspended in buffer and stored. The PCRs were carried out using primers for amplification of the EBV BamM region. Positive and negative controls were added to each reaction. The PCR products were used for direct sequencing for confirmation. RESULTS: The viral sequences were positive in 11/75 (14.7%) of our samples. CONCLUSION: The prevalence of EBV DNA was 11/75 (14.7%) in our glioma collection. Further molecular and epidemiological studies are needed to establish the possible role played by EBV in the tumorigenesis of gliomas.